68Ga-DOTATATE PET/CT in Primary Hepatic Neuroendocrine Tumor. (February 2017) - Gorla, Arun Kumar Reddy; Basher, Rajender Kumar; Kaman, Lileshwar; Bal, Amanjit; Bhattacharya, Anish; Mittal, Bhagwant Rai
Abstract : Abstract: Primary neuroendocrine tumors of the liver are a diagnostic challenge. We present a rare case of primary hepatic neuroendocrine tumor in which 68 Ga-DOTATATE PET/CT imaging played an important role in the diagnosis and follow-up.